Study Of The Legal Responsibility Of Developers For The Provision Of Public Facilities And Social Facilities - M.Ali Iskandar; Rafli Wahyu Indrianto; Moh Abyan Nurfikri; Agus Dimyati; Anom Sutrisno (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
The enforcement of law is an integral aspect of the legal system's functioning, and it is often criticized with phrases like "no viral, no justice" or "law is sharp downwards, blunt upwards." In this context, how does the philosophy of law play a role in upholding the integrity of law enforcement, and how can a legal enforcement system be grounded in the rationality of legal philosophy. The provision of public facilities and social facilities in housing is needed for the welfare and comfort of the community in housing. The provision of these facilities involves developers and the Government. In accordance with Cirebon Regency Regional Regulation No. 7 of 2015 the implementation of the provision of infrastructure and facilities in housing refers to the principles of openness, accountability, legal certainty, partiality, and sustainability. In connection with this, the purpose of this paper is to be able to find out the Developer's responsibility in carrying out the procurement of public facilities and social facilities as a condition of submission of housing to the Local Government. The method of approach used here is socio-legal which is associated with social problems. Related to the management of infrastructure and facilities in housing is still a problem, namely the developer has not submitted housing facilities to the Local Government. This happened due to the default of the developer to consumers and the lack of assertiveness of the Regional Government in implementing Government Regulation No. 6 of 2015.